Effect of primer selection on estimates of GB virus C (GBV-C) prevalence and response to antiretroviral therapy for optimal testing for GBV-C viremia (vol 44, pg 3105, 2006) - Souza, I. E. [UNIFESP] (2006)
Univ Iowa, Dept Internal Med, Roy & Lucille Carver Coll Med, Iowa City, IA 52242 USA